Molecular sieve based flame-retardant material and preparation method thereof
By using a combination of hollow molecular sieve and flame retardant, the problems of dispersion, compatibility, processing difficulty, brittleness, high cost and limited flame retardant efficiency of existing molecular sieve-based flame retardant materials are solved, and the high thermal stability, flame retardant and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202411646679.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing molecular sieve-based flame retardant materials have problems such as poor dispersion, poor compatibility with the matrix, high processing difficulty, increased material brittleness, high cost and limited flame retardant efficiency.
The combination of hollow molecular sieve and flame retardant is used to prepare hollow molecular sieve by hydrothermal method, and the flame retardant is coated or embedded in the micropores and hollow structures of the hollow molecular sieve to improve the flame retardant performance and mechanical properties of the material.
It significantly improves the thermal stability, flame retardancy and fire resistance of the material, reduces the generation of toxic gases and smoke, improves the mechanical properties and processing properties of the material, and reduces production costs.
Smart Images

Figure CN119505372A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a flame retardant material, in particular to a molecular sieve-based flame retardant material and a preparation method thereof. Background Art
[0002] In the field of security, especially for bank-specific steel plate protective walls, due to their particularity, they need to have not only strong explosion-proof and anti-theft performance, but also strong fireproof performance. For example, the application number is: 202223122677.1, the patent name is: a steel plate wall module and a fireproof and heat-insulating steel plate protective wall, which uses conventional fireproof layer coatings and fireproof and heat-insulating layers inside. The overall thickness is large, the cost will be relatively high, and the actual fireproof performance is not good enough.
[0003] Molecular sieve-based flame retardant materials are a type of composite material that combines molecular sieves with polymer matrices to improve the heat resistance, smoke suppression and flame retardancy of the material. Molecular sieves, due to their regular microporous structure, large specific surface area and excellent adsorption properties, can play a physical barrier and catalytic role in the combustion process of materials, reduce heat transfer and promote the formation of a carbonized layer. In recent years, the application of nanomolecular sieves has further improved the performance of flame retardant materials, with better dispersibility and surface activity. In addition, with the improvement of environmental protection requirements, molecular sieve-based flame retardant materials are gradually combined with halogen-free environmentally friendly flame retardants, becoming an important direction for the development of green and efficient flame retardant materials, and are widely used in electronic appliances, building materials and other fields.
[0004] The molecular sieve-based flame retardant materials that have been developed so far mainly include various materials composited with molecular sieves and polymer matrices. The flame retardant effect is usually enhanced by synergizing molecular sieves with traditional flame retardants (such as phosphorus-based, nitrogen-based, etc.).
[0005] 1. Molecular sieve / polyethylene composite materials: By adding molecular sieve to polyethylene, its thermal stability and smoke suppression performance can be improved. The microporous structure of the molecular sieve forms a physical barrier during the combustion process, hindering the transfer of heat and oxygen and reducing the combustion rate.
[0006] 2. Molecular sieve / polypropylene composite material: Polypropylene is a common thermoplastic material, but its flame retardancy is poor. After adding molecular sieve, the heat resistance and flame retardancy of the material are significantly improved, and the molecular sieve can promote the formation of the carbonized layer, further enhancing the fire resistance.
[0007] 3. Molecular sieve / epoxy resin composite materials: Epoxy resin is widely used in the fields of electronics and construction. By introducing molecular sieves, the thermal stability and flame retardancy of epoxy resin are greatly improved, and the presence of molecular sieves helps to reduce the release of toxic fumes.
[0008] 4. Nano-molecular sieve-based materials: Nano-molecular sieves have a larger specific surface area and show better flame retardant effects. Nano-molecular sieves are more compatible with polymer matrices and can significantly enhance the mechanical properties and heat resistance of materials.
[0009] Although molecular sieve-based flame retardant materials have significant advantages in flame retardant properties, there are still some disadvantages and challenges:
[0010] 1. Poor dispersion: Molecular sieves have poor dispersion in polymer matrix and are prone to agglomeration, which affects the uniformity of the material. Especially in nano molecular sieves, the agglomeration problem is more prominent, which will weaken its flame retardant effect and reduce the mechanical properties of the composite material.
[0011] 2. Poor compatibility with the matrix: Molecular sieves are inorganic materials and have poor interfacial compatibility with organic polymer matrices, which may lead to interfacial defects and affect the overall performance of the material, such as mechanical strength and toughness. Surface modification of molecular sieves is required to improve their bonding with the matrix.
[0012] 3. Difficult processing: The processing technology of molecular sieve-based flame retardant materials is complicated, especially the use of nano molecular sieves requires precise dispersion and compounding technology. The preparation process of materials often requires complex surface treatment and addition steps, which increases production costs and difficulty.
[0013] 4. Increased material brittleness: A high content of molecular sieve in the composite material may increase the brittleness of the material and reduce the toughness and impact resistance of the material, which limits its scope of use in practical applications.
[0014] 5. High cost: The production cost of molecular sieves, especially those that have been modified or nano-processed, is high, which limits their large-scale application in some cost-sensitive fields. The preparation of high-performance molecular sieve-based flame retardant materials requires relatively expensive processes, which increases the overall production cost.
[0015] 6. Limited flame retardant efficiency: Although molecular sieves perform well in some aspects, their flame retardant efficiency may not be as good as some traditional high-efficiency flame retardants, such as halogen flame retardants, when used alone. Therefore, it usually needs to be used in combination with other flame retardants to achieve the ideal flame retardant effect. Summary of the invention
[0016] The purpose of the present invention is to provide a molecular sieve-based flame retardant material and a preparation method thereof. By using the material and the method, the thermal stability, flame retardancy and fire resistance of the material are effectively improved, and the generation of toxic gases and smoke can also be reduced.
[0017] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: a molecular sieve-based flame retardant material, including a hollow molecular sieve and a flame retardant, wherein the hollow molecular sieve is a hollow structure with micropores, and the flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the crystal surface of the hollow molecular sieve.
[0018] In the above technical solution, the flame retardant includes organic phosphorus flame retardant, aluminum hydroxide, magnesium hydroxide or other inorganic flame retardants.
[0019] The present invention also provides a method for preparing a hollow molecular sieve, which is used to prepare the hollow molecular sieve in the molecular sieve-based flame retardant material, and the steps are:
[0020] S1. Preparation of a mixture: The mixture is prepared from a silicon source and a structure directing agent;
[0021] S2. Preparation of precursor I: hydrothermally crystallizing the mixture to obtain precursor I;
[0022] S3, calcination: calcining the precursor I in air;
[0023] S4, finished product: the precursor I calcined in step S3 is etched in a structure directing agent solution, and then dried to obtain a hollow molecular sieve;
[0024] The silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate, and the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide.
[0025] In the above technical solution, the steps for preparing the mixture are as follows:
[0026] A1. Stir the silicon source and the structure directing agent evenly to obtain solution I;
[0027] A2, deionized water is added to solution I and stirred to obtain a solution, wherein the solution is the mixture;
[0028] In the step A1, the silicon source and the structure directing agent are mixed, and stirred at 25° C. for 0.5 h to 2 h to obtain solution I;
[0029] In the step A2, deionized water is added to solution I, and the mixture is stirred at 25° C. for 0.5 h to 1 h to obtain a solution.
[0030] In the above technical solution, in step S2, the mixture is hydrothermally crystallized at 80°C to 200°C for 8h to 96h;
[0031] and / or, the precursor I is calcined at 500° C. to 700° C. for 4 h to 8 h;
[0032] and / or, the precursor I is calcined in a muffle furnace at 500° C. to 700° C. for 4 h to 8 h;
[0033] In the above technical solution, step S4 includes the following steps:
[0034] B1, mixing the calcined precursor I with a structure directing agent solution to perform an etching reaction;
[0035] The etching reaction is stirred at 50° C. to 170° C. for 1 h to 48 h;
[0036] B2, separating the molecular sieve from the solution after the etching reaction by centrifugation or filtration;
[0037] B3, washing the separated molecular sieve with deionized water to remove the residual structure directing agent solution and reaction by-products;
[0038] B4. Centrifuge the molecular sieve after washing in B3 to separate the solid, and then dry it in an oven at 60° C. to 90° C. to obtain a hollow molecular sieve.
[0039] In the above technical solution, the structure directing agent solution is a solution containing a structure directing agent, the molar concentration of the solution containing the structure directing agent is 0.1M to 2M, and the feed ratio of the precursor I to the structure directing agent solution is 1g / 10ml.
[0040] In the above technical solution, in step B4, after the solid is dried in an oven, the hollow molecular sieve is calcined at a temperature of 500° C. to 700° C. for a time of 1 h to 8 h.
[0041] The present invention also provides a method for preparing a molecular sieve-based flame retardant material, which is used to prepare the above-mentioned molecular sieve-based flame retardant material, and the steps are:
[0042] C1. Introducing the flame retardant into the hollow molecular sieve by impregnation or dissolution, so that the flame retardant is partially adsorbed in the micropores and / or on the surface of the hollow molecular sieve;
[0043] C2. Mixing the hollow molecular sieve containing the flame retardant with the crystallization solution, and performing a hydrothermal recrystallization reaction at 120° C. to 180° C. for 12 h to 48 h, so that the crystal structure of the hollow molecular sieve is rearranged, the micropores are reconstructed to form a hollow structure, and the flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the surface of the hollow molecular sieve crystals;
[0044] C3. After the recrystallization reaction is completed, the sample is separated by filtration or centrifugation, and the sample is washed with deionized water to remove the unreacted crystallization solution;
[0045] C4. Drying the sample separated in step C3 to obtain a molecular sieve-based flame retardant material.
[0046] In the above technical solution, a structure directing agent and an alkaline solution are added to the crystallization solution;
[0047] And / or, the crystallization solution is an aqueous solution containing a silicon source;
[0048] And / or, the silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate; the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide; the alkaline solution is a NaOH solution or a KOH solution;
[0049] In step C3, the sample is washed with deionized water to remove unreacted crystallization solution, alkaline solution and structure directing agent.
[0050] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0051] 1. The molecular sieve-based flame retardant material prepared by the corresponding process in the present invention has thermal stability and flame retardancy, can reduce the generation of toxic gases and smoke, and can also improve the mechanical properties and processing properties of the material;
[0052] 2. The hollow molecular sieve of the present invention has high thermal stability and fire resistance, can effectively insulate and inhibit combustion reactions under high temperature conditions, and at the same time, the hollow structure can increase the loading amount of the flame retardant and slowly release the flame retardant components during the combustion process, thereby significantly improving the flame retardant properties of the composite material;
[0053] 3. The micropores and hollow structure of the hollow molecular sieve in the present invention can absorb harmful gases such as CO, CO2 and organic volatiles generated during combustion, reduce the generation of toxic smoke, improve the environmental performance of the material, and effectively enhance the safety of flame retardant materials, especially for applications in construction and transportation.
[0054] 4. The hollow molecular sieve of the present invention can enhance the compatibility between the flame retardant and the matrix material by coating the flame retardant, reduce the negative impact of the flame retardant on the material (such as reducing the mechanical strength or affecting the flexibility), and at the same time, the structure of the hollow molecular sieve can improve the strength and toughness of the composite material, and maintain the excellent mechanical properties and processability of the material;
[0055] 5. The hollow molecular sieve in the present invention has a larger surface area than the traditional solid molecular sieve due to its unique internal and external pore structure, reduces the tendency of agglomeration between particles, and has better dispersibility, making it more evenly distributed in the polymer matrix, thereby improving the flame retardant effect and mechanical properties of the material;
[0056] 6. The hollow molecular sieve in the present invention has a larger surface area, and the interaction with the polymer matrix can be increased by surface modification (such as organic treatment). Such treatment can enhance the interfacial bonding between the two, reduce interfacial defects, and thus improve the overall mechanical properties of the composite material, thereby effectively improving the compatibility with the matrix;
[0057] 7. The lightweight structure of the hollow molecular sieve in the present invention makes it easier to mix and disperse during processing, especially at the nanoscale, it can be better integrated into the polymer matrix, reducing the need for complex processing technology, reducing production difficulty, and improving processing efficiency;
[0058] 8. The structure of the hollow molecular sieve in the present invention is more flexible and lightweight than that of the traditional solid molecular sieve, which helps to reduce the brittleness of the composite material. Its low-density structure can mitigate the adverse effects on the mechanical properties of the material and maintain good toughness and impact resistance;
[0059] 9. In the present invention, since the hollow molecular sieve has a high specific surface area and high flame retardant performance, the ideal flame retardant effect can be achieved by using less hollow molecular sieve, and its higher efficiency can reduce the overall material usage, thereby reducing production costs;
[0060] 10. The double pore structure of the hollow molecular sieve in the present invention improves the catalytic efficiency, can more effectively promote the formation of the carbonized layer, and at the same time prevent the transfer of heat and oxygen, significantly improving the flame retardant effect of the material. Compared with traditional molecular sieves, the flame retardant efficiency is higher and the dependence on other flame retardants is reduced; by introducing the hollow molecular sieve, not only can the multiple shortcomings of traditional molecular sieve-based flame retardant materials be solved, but also the comprehensive performance of the material can be further improved, promoting its widespread use in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 is the XRD pattern of the traditional S-1 prepared in the embodiment of the present invention;
[0062] Figure 2 Transmission electron microscopy images of hollow S-1 coated with flame retardant tris(β-chloroethyl) phosphate prepared by recrystallization using different TPAOH concentrations;
[0063] Figure 3 This is a scanning electron microscope image of Beta molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate;
[0064] Figure 4 This is a scanning electron microscope image of the flame retardant tri(β-chloroethyl) phosphate coated with nanosheet SP-S-1 molecular sieve. DETAILED DESCRIPTION
[0065] The present invention will be further described below in conjunction with the accompanying drawings and embodiments:
[0066] Embodiment 1: A molecular sieve-based flame retardant material comprises a hollow molecular sieve and a flame retardant, wherein the hollow molecular sieve is a hollow structure with micropores, and the flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the crystal surface of the hollow molecular sieve.
[0067] In the present invention, micropores are in the hollow molecular sieve, and the outer end of the micropores will be connected to the outer surface of the hollow molecular sieve, and the flame retardant will be coated in the micropores and hollow structure of the hollow molecular sieve, or the flame retardant will be coated in the crystal surface of the hollow molecular sieve, or the flame retardant will be coated in the micropores and hollow structure of the hollow molecular sieve, and coated in the crystal surface of the hollow molecular sieve. Or the flame retardant will be embedded in the micropores and hollow structure of the hollow molecular sieve, or the flame retardant will be embedded in the crystal surface of the hollow molecular sieve, or the flame retardant will be embedded in the micropores and hollow structure of the hollow molecular sieve, and embedded in the crystal surface of the hollow molecular sieve. With this structure, the hollow molecular sieve has high thermal stability and fire resistance, can effectively insulate and suppress combustion reaction under high temperature conditions, and at the same time, the hollow structure can increase the load of the flame retardant, and slowly release the flame retardant component during the combustion process, thereby significantly improving the flame retardant properties of the composite material. The micropores and hollow structure of hollow molecular sieves can absorb harmful gases such as CO, CO2 and organic volatiles generated during combustion, reduce the generation of toxic smoke, and improve the environmental performance of materials, which is very important for improving the safety of flame retardant materials, especially in the fields of construction and transportation. Hollow molecular sieves can enhance the compatibility between flame retardants and matrix materials and reduce the negative impact of flame retardants on materials (such as reducing mechanical strength or affecting flexibility) by coating or embedding, coating and embedding flame retardants. At the same time, the structure of hollow molecular sieves can improve the strength and toughness of composite materials and maintain the excellent mechanical properties and processability of materials.
[0068] The flame retardant includes organic phosphorus flame retardant, aluminum hydroxide, magnesium hydroxide or other inorganic flame retardant, and has good flame retardant performance.
[0069] The present invention also provides a method for preparing a hollow molecular sieve, which is used to prepare the hollow molecular sieve in the molecular sieve-based flame retardant material, and the steps are:
[0070] S1. Preparation of a mixture: The mixture is prepared from a silicon source and a structure directing agent;
[0071] S2. Preparation of precursor I: hydrothermally crystallizing the mixture to obtain precursor I;
[0072] S3, calcination: calcining the precursor I in air;
[0073] S4, finished product: the precursor I calcined in step S3 is etched in a structure directing agent solution, and then dried to obtain a hollow molecular sieve;
[0074] The silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate, and the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide.
[0075] The content of SiO2 in the silicon source is 40wt%. The molar ratio of the silicon source to the structure directing agent is 1:0.3-0.4. The molar number of the silicon source is counted as the molar number of SiO2. The molar number of the structure directing agent is counted as the molar number of the structure directing agent itself.
[0076] The preparation steps of the mixture are as follows:
[0077] A1. Stir the silicon source and the structure directing agent evenly to obtain solution I;
[0078] A2, deionized water is added to solution I and stirred to obtain a solution, wherein the solution is the mixture;
[0079] In the step A1, the silicon source and the structure directing agent are mixed, and stirred at 25° C. for 0.5 h to 2 h to obtain solution I;
[0080] In the step A2, deionized water is added to solution I, and the mixture is stirred at 25° C. for 0.5 h to 1 h to obtain a solution.
[0081] In step S2, the mixture is hydrothermally crystallized at 80°C to 200°C for 8 to 96 hours; optionally, the upper limit of the hydrothermal crystallization temperature is 170°C or 190°C, and the lower limit is 80°C or 90°C. The upper limit of the hydrothermal crystallization time is 72 hours or 96 hours, and the lower limit is 8 hours or 24 hours.
[0082] The precursor I is calcined at 500°C to 700°C for 4h to 8h;
[0083] The precursor I is calcined in a muffle furnace at 500°C to 700°C for 4 to 8 hours. The upper limit of the calcination temperature is 650°C or 700°C, the lower limit is 500°C or 550°C, the upper limit of the calcination time is 6 hours or 8 hours, and the lower limit is 4 hours or 5 hours.
[0084] As a specific embodiment, the muffle furnace cavity is 30 cm long, 20 cm wide, and 14 cm high, and the filler weight is 1 g to 6 g.
[0085] In step S2, the hydrothermal crystallization process is as follows: deionized water is added to the mixture and stirred at a temperature of 25°C to 30°C for 1h to 5 hours, then placed in a reactor, and then the reactor is placed in an oven for constant temperature crystallization at 80°C to 100°C for 8h to 96h. After naturally cooling to room temperature, the substances in the reactor are centrifuged to separate the solids, and the solids are repeatedly washed with deionized water until neutral, and then dried in an oven at 60°C to 100°C to obtain precursor I.
[0086] The precursor I after calcination constitutes a molecular sieve. Therefore, in order to prepare the molecular sieve into a hollow structure with micropores, step S4 is also included.
[0087] The step S4 includes the following steps:
[0088] B1, mixing the calcined precursor I with a structure directing agent solution to perform an etching reaction;
[0089] The etching reaction is stirred at 50° C. to 170° C. for 1 h to 48 h;
[0090] B2, separating the molecular sieve from the solution after the etching reaction by centrifugation or filtration;
[0091] B3, washing the separated molecular sieve with deionized water to remove the residual structure directing agent solution and reaction by-products;
[0092] B4. Centrifuge the molecular sieve after washing in B3 to separate the solid, and then dry it in an oven at 60° C. to 90° C. to obtain a hollow molecular sieve.
[0093] The structure directing agent solution is a solution containing a structure directing agent, the molar concentration of the solution containing the structure directing agent is 0.1M (mol / L) to 2M (mol / L), and the feed ratio of the precursor I to the structure directing agent solution is 1g / 10ml.
[0094] The upper limit of the molar concentration of the solution containing the structure directing agent is selected from 1.5 mol / L or 1.75 mol / L, and the lower limit is selected from 0.1 mol / L or 0.2 mol / L.
[0095] In this embodiment, before the calcined precursor I is mixed with the structure directing agent solution, the precursor I is dried in advance to ensure that the moisture in the micropores and the hollow structure is removed to improve the uniformity of the subsequent etching reaction. In this embodiment, during the etching reaction of the precursor I mixed with the structure directing agent solution, the structure directing agent solution not only acts as a template, but also etches the surface and micropores (channels) of the molecular sieve through alkaline action to change its microstructure. During the etching process, the silicon skeleton part of the molecular sieve is preferentially dissolved, so that the micropore part is converted into a mesoporous or macroporous structure, thereby enhancing the diffusion performance of the molecular sieve.
[0096] More preferably, or optionally, in step B4, after the solid is dried in an oven, the hollow molecular sieve is calcined at a temperature of 500° C. to 700° C. for a time of 1 h to 8 h.
[0097] The purpose of calcination is to remove the organic structure directing agent, restore the micropore (or pore) structure of the molecular sieve, form a relatively pure micropore (or pore) structure, and further improve the thermal stability and catalytic performance of the material.
[0098] The present invention also provides a method for preparing a molecular sieve-based flame retardant material, which is used to prepare the above-mentioned molecular sieve-based flame retardant material, and the steps are:
[0099] C1. Introducing the flame retardant into the hollow molecular sieve by impregnation or dissolution, so that the flame retardant is partially adsorbed in the micropores and / or on the surface of the hollow molecular sieve;
[0100] C2. Mixing the hollow molecular sieve containing the flame retardant with the crystallization solution, and performing a hydrothermal recrystallization reaction at 120° C. to 180° C. for 12 h to 48 h, so that the crystal structure of the hollow molecular sieve is rearranged, the micropores are reconstructed to form a hollow structure, and the flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the surface of the hollow molecular sieve crystals;
[0101] In this process, the crystal structure of the hollow molecular sieve is rearranged and the micropores (or channels) are reconstructed to form a hollow structure.
[0102] C3. After the recrystallization reaction is completed, the sample is separated by filtration or centrifugation, and the sample is washed with deionized water to remove the unreacted crystallization solution;
[0103] C4. Drying the sample separated in step C3 to obtain a molecular sieve-based flame retardant material. In this step, the stability of the hollow molecular sieve can be further enhanced.
[0104] Wherein, a structure directing agent and an alkaline solution are added to the crystallization solution;
[0105] The crystallization solution is an aqueous solution containing a silicon source;
[0106] The silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate; the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide; the alkaline solution is a NaOH solution or a KOH solution;
[0107] In step C3, the sample is washed with deionized water to remove unreacted crystallization solution, alkaline solution and structure directing agent.
[0108] Example 2: A method for preparing a molecular sieve-based flame retardant material (hollow S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps are:
[0109] 1) 8.32 g of TEOS (tetraethyl orthosilicate) solution was mixed with 7.808 g of TPAOH (tetrapropylammonium hydroxide solution) solution, and the mixture was diluted by stirring at 25° C. for 1 hour;
[0110] 2) Add 8.52 g of deionized water to the above solution and stir at 25°C for 5 hours;
[0111] 3) The solution obtained in step 2) is transferred to a stainless steel reactor, and then the reactor is placed in an oven at 90° C. for crystallization for 48 hours; after the crystallization is completed, the reactor is taken out, and after natural cooling to room temperature, the solid product is separated by centrifugation, and the solid product is repeatedly washed with deionized water until it is neutral, and then dried in an oven at 80° C. to obtain the traditional S-1 raw powder;
[0112] 4) calcining 1 g of the conventional S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain conventional S-1-C (calcined sample);
[0113] 5) adding the conventional S-1-C obtained in step 4) to a 0.2M (mol / L) TPAOH solution and stirring for 1 hour for pretreatment (the mass ratio of conventional S-1-C to TPAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60 to 90°C;
[0114] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores (micropores) or surface of the molecular sieve;
[0115] 7) Preparation of recrystallization solution: prepare a crystallization solution containing a silicon source (such as silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 0.2M (mol / L) TPAOH solution;
[0116] 8) Recrystallization reaction: The molecular sieve containing the flame retardant is mixed with the crystallization solution and subjected to a hydrothermal recrystallization reaction at 90°C. During this process, the crystal structure of the molecular sieve is rearranged and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0117] Example 3: A method for preparing a molecular sieve-based flame retardant material (hollow S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps of which are:
[0118] 1) 8.32 g of TEOS (tetraethyl orthosilicate) solution was mixed with 7.808 g of TPAOH (tetrapropylammonium hydroxide solution) solution, and the mixture was diluted by stirring at 25° C. for 1 hour;
[0119] 2) Add 8.52 g of deionized water to the above solution and stir at 25°C for 5 hours;
[0120] 3) The solution obtained in step 2) is transferred to a stainless steel reactor, and then the reactor is placed in an oven at 90° C. for crystallization for 48 hours; after the crystallization is completed, the reactor is taken out, and after natural cooling to room temperature, the solid product is separated by centrifugation, and the solid product is repeatedly washed with deionized water until it is neutral, and then dried in an oven at 80° C. to obtain the traditional S-1 raw powder;
[0121] 4) calcining 1 g of the conventional S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain conventional S-1-C (calcined sample);
[0122] 5) The conventional S-1-C obtained in step 4) was added to a 0.2M (mol / L) TPAOH solution and stirred for 1 hour for pretreatment (the mass ratio of conventional S-1-C to TPAOH solution was 1:10), the treated sample was centrifuged to separate the solid, and then dried in an oven at 60 to 90°C.
[0123] 6) 2 g of flame retardant tris(β-chloroethyl) phosphate was introduced into the pretreated molecular sieve by dissolution method (the solvent was ethanol), so that it was partially adsorbed on the pores or surface of the molecular sieve.
[0124] 7) Preparation of recrystallization solution: Prepare a crystallization solution containing a silicon source (such as silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 0.4M (mol / L) TPAOH solution.
[0125] 8) Recrystallization reaction: The molecular sieve containing the flame retardant is mixed with the crystallization solution and subjected to a hydrothermal recrystallization reaction at 90°C. During this process, the crystal structure of the molecular sieve is rearranged and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0126] Example 4: A method for preparing a molecular sieve-based flame retardant material (hollow S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps of which are:
[0127] 1) Mix 8.32 g of TEOS (tetraethyl orthosilicate) solution and 7.808 g of TPAOH (tetrapropylammonium hydroxide solution) solution, and dilute by stirring at 25° C. for 1 hour;
[0128] 2) Add 8.52 g of deionized water to the above solution and stir at 25°C for 5 hours;
[0129] 3) The solution obtained in step 2) is transferred to a stainless steel reactor, and then the reactor is placed in an oven at 90° C. for crystallization for 48 hours; after the crystallization is completed, the reactor is taken out, and after natural cooling to room temperature, the solid product is separated by centrifugation, and the solid product is repeatedly washed with deionized water until it is neutral, and then dried in an oven at 80° C. to obtain the traditional S-1 raw powder;
[0130] 4) calcining 1 g of the conventional S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain conventional S-1-C (calcined sample);
[0131] 5) adding the conventional S-1-C obtained in step 4) to a 0.2M TPAOH solution and stirring for 1 hour for pretreatment (the mass ratio of conventional S-1-C to TPAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60 to 90°C;
[0132] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores or surface of the molecular sieve;
[0133] 7) Preparation of recrystallization solution: Prepare a crystallization solution containing a silicon source (such as silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 0.8M (mol / L) TPAOH solution.
[0134] 8) Recrystallization reaction: The molecular sieve containing flame retardant is mixed with the crystallization solution and subjected to hydrothermal recrystallization reaction at a certain temperature of 90°C. During this process, the crystal structure of the molecular sieve is rearranged and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0135] Example 5: A method for preparing a molecular sieve-based flame retardant material (hollow S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps of which are:
[0136] 1) Mix 8.32 g of TEOS solution with 7.808 g of TPAOH solution and dilute by stirring at 25°C for 1 hour;
[0137] 2) Add 8.52 g of deionized water to the above solution and stir at 25°C for 5 hours;
[0138] 3) The solution obtained in step 2) is transferred to a stainless steel reactor, and then the reactor is placed in an oven at 90°C for crystallization for 48 hours; after the crystallization is completed, the reactor is taken out, and after natural cooling to room temperature, the substance in the reactor is centrifuged to separate the solid product, and the solid product is repeatedly washed with deionized water until it is neutral, and then dried in an oven at 80°C to obtain the traditional S-1 raw powder.
[0139] 4) calcining 1 g of the conventional S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain conventional S-1-C (calcined sample);
[0140] 5) adding the conventional S-1-C obtained in step 4) to a 0.2M TPAOH solution and stirring for 1 hour for pretreatment (the mass ratio of conventional S-1-C to TPAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60 to 90°C;
[0141] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores or surface of the molecular sieve;
[0142] 7) Preparation of recrystallization solution: prepare a crystallization solution containing a silicon source (such as silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 1.5M TPAOH solution;
[0143] 8) Recrystallization reaction: The molecular sieve containing the flame retardant is mixed with the crystallization solution and subjected to a hydrothermal recrystallization reaction at a certain temperature of 90°C. During this process, the crystal structure of the molecular sieve is rearranged, and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0144] Example 6: A method for preparing a molecular sieve-based flame retardant material (hollow S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps are:
[0145] 1) Mix 8.32 g of TEOS solution with 7.808 g of TPAOH solution and dilute by stirring at 25°C for 1 hour;
[0146] 2) Add 8.52 g of deionized water to the above solution and stir at 25°C for 5 hours;
[0147] 3) The solution obtained in step 2) is transferred to a stainless steel reactor, and then the reactor is placed in an oven at 90° C. for crystallization for 48 hours; after the crystallization is completed, the reactor is taken out, and after natural cooling to room temperature, the solid product is separated by centrifugation, and the solid product is repeatedly washed with deionized water until it is neutral, and then dried in an oven at 80° C. to obtain the traditional S-1 raw powder;
[0148] 4) calcining 1 g of the conventional S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain conventional S-1-C (calcined sample);
[0149] 5) adding the conventional S-1-C obtained in step 4) to a 0.2M TPAOH solution and stirring for 1 hour for pretreatment (the mass ratio of conventional S-1-C to TPAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60 to 90°C;
[0150] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores or surface of the molecular sieve;
[0151] 7) Preparation of recrystallization solution: prepare a crystallization solution containing a silicon source (such as silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 2M TPAOH solution;
[0152] 8) Recrystallization reaction: The molecular sieve containing the flame retardant is mixed with the crystallization solution and subjected to a hydrothermal recrystallization reaction at a certain temperature of 90°C. During this process, the crystal structure of the molecular sieve is rearranged, and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0153] Example 7: A method for preparing a molecular sieve-based flame retardant material (Beta molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps of which are:
[0154] 1) 6.74 g of tetraethylammonium hydroxide (TEAOH) solution, 0.106 g of cesium chloride and 0.066 g of sodium aluminate were added to 25 mL of polytetrafluoroethylene liner and stirred at room temperature for 10 min. Subsequently, 2.4 g of white carbon black was gradually added to the above solution in three times, and kept heated and stirred in an 80°C oil bath, and further 350 μL of hydrofluoric acid solution was added dropwise;
[0155] 2) the synthetic gel obtained in step 1) was stirred at room temperature overnight and then placed in a stainless steel autoclave for static crystallization at 140° C. for 4 days;
[0156] 3) The crystallized sample was centrifuged and washed, and the obtained solid product was dried in an oven at 80° C. overnight to obtain Beta molecular sieve raw powder.
[0157] 4) calcining 1 g of the Beta molecular sieve powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping the temperature at 550° C. for 6 hours to obtain Beta-C (calcined sample);
[0158] 5) adding the conventional Beta-C obtained in step 4) to a 0.2M TEAOH solution and stirring for 1 hour for pretreatment (the mass ratio of Beta-C to TEAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60-90°C;
[0159] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores or surface of the molecular sieve;
[0160] 7) Preparation of recrystallization solution: prepare a crystallization solution containing a silicon source (such as white carbon black, silica sol, sodium silicate, sodium aluminate, tetraethyl silicate, etc.), and add a certain amount of 0.2M TEAOH solution.
[0161] 8) Recrystallization reaction: The molecular sieve containing flame retardant is mixed with the crystallization solution and subjected to hydrothermal recrystallization reaction at a certain temperature of 140°C. During this process, the crystal structure of the molecular sieve is rearranged and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0162] Example 8: A method for preparing a molecular sieve-based flame retardant material (nanosheet S-1 molecular sieve coated with flame retardant tris(β-chloroethyl) phosphate), the steps of which are:
[0163] 1) Add 18.69 g of tetrabutylammonium hydroxide (TBAOH) solution into a 50 mL beaker, then add 12.49 g of tetraethyl silicate, and stir at room temperature for 6 h to completely hydrolyze to obtain a uniform transparent solution;
[0164] 2) transferring the mixed solution of step 1) into a 100 mL polytetrafluoroethylene-lined stainless steel autoclave and statically crystallizing at 140° C. for 2 days;
[0165] 3) centrifuging and washing the sample after crystallization in step 2), and drying the obtained solid product in an oven at 80° C. overnight to obtain nanosheet SP-S-1 raw powder;
[0166] 4) calcining 1 g of the nanosheet SP-S-1 molecular sieve raw powder obtained in step 3) in a muffle furnace, heating to 550° C. for 4 hours, and then keeping at 550° C. for 6 hours to obtain nanosheet SP-S-1-C (calcined sample);
[0167] 5) adding the nanosheet SP-S-1-C obtained in step 4) to a 0.2M TBAOH solution and stirring for 1 hour for pretreatment (the mass ratio of the nanosheet SP-S-1-C to the TBAOH solution is 1:10), centrifuging the treated sample to separate the solid, and then drying it in an oven at 60-90°C;
[0168] 6) introducing 2 g of flame retardant tris(β-chloroethyl) phosphate into the pretreated molecular sieve by dissolution method (the solvent is ethanol), so that it is partially adsorbed on the pores or surface of the molecular sieve;
[0169] 7) Preparation of recrystallization solution: prepare a crystallization solution containing a silicon source (such as tetraethyl silicate, white carbon black, silica sol, sodium silicate, sodium aluminate, etc.), and add a certain amount of 0.2M TBAOH solution;
[0170] 8) Recrystallization reaction: The molecular sieve containing the flame retardant is mixed with the crystallization solution and subjected to a hydrothermal recrystallization reaction at a certain temperature of 140°C. During this process, the crystal structure of the molecular sieve is rearranged and the pores are reconstructed to form a hollow structure. The flame retardant is coated or embedded in the hollow structure or crystal surface of the molecular sieve.
[0171] The composite flame retardant prepared in Examples 2-8 was added to polypropylene at 5 wt% by mass through melt kneading to obtain flame retardant composite materials. The flame retardant composite materials were subjected to the following tests. The test results are shown in Table 1.
[0172] (1) Flame retardant performance: According to UL94 standard, vertical combustion test was carried out on it.
[0173] (2) Limiting oxygen index: tested in accordance with GBT 2406.2 standard.
[0174] (3) Smoke density: Tested in accordance with GB / T 8323.2 standard
[0175] Table 1:
[0176] Flame retardant grade Smoke Density Rating (SDR) Limiting oxygen index % Example 2 UL94-V0 60 28.5 Example 3 UL94-V0 59 28.7 Example 4 UL94-V0 57 29.6 Example 5 UL94-V0 57 29.9 Example 6 UL94-V0 56 30.3 Example 7 UL94-V0 58 28.6 Example 8 UL94-V0 56 28.9
[0177] From the data in Table 1, it can be seen that the composite flame retardant is excellent in thermal stability and flame retardant properties in polypropylene composite materials. With the increase of TPAOH concentration in the recrystallization solution, the etched pore size becomes smaller, the number increases, the etching is more uniform, and the smoke produced by combustion is better adsorbed. At the same time, because more tris(β-chloroethyl) phosphate is coated in the interior of the molecular sieve where oxygen is difficult to reach, the limiting oxygen index of the flame retardant material is also increased.
[0178] In this document, the terms "comprises," "comprising," or any other variations thereof, are intended to cover a non-exclusive inclusion of elements other than those listed and may also include additional elements not expressly listed.
[0179] In this document, the directional words such as front, back, top, and bottom are defined by the positions of the components in the drawings and the positions of the components relative to each other, and are only for the sake of clarity and convenience in expressing the technical solution. It should be understood that the use of the directional words should not limit the scope of protection claimed in this application.
[0180] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0181] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A molecular sieve-based flame retardant material, characterized in that: The invention comprises a hollow molecular sieve and a flame retardant. The hollow molecular sieve is a hollow structure with micropores. The flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the crystal surface of the hollow molecular sieve.
2. The molecular sieve-based flame retardant material according to claim 1, characterized in that: The flame retardant includes organic phosphorus flame retardant, aluminum hydroxide, magnesium hydroxide or other inorganic flame retardants.
3. A method for preparing a hollow molecular sieve, characterized in that: The hollow molecular sieve used for preparing the molecular sieve-based flame retardant material according to any one of claims 1 to 2 comprises the following steps: S1. Preparation of a mixture: The mixture is prepared from a silicon source and a structure directing agent; S2. Preparation of precursor I: hydrothermally crystallizing the mixture to obtain precursor I; S3, calcination: calcining the precursor I in air; S4, finished product: the precursor I calcined in step S3 is etched in a structure directing agent solution, and then dried to obtain a hollow molecular sieve; The silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate, and the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide.
4. The method for preparing the hollow molecular sieve according to claim 3, characterized in that: The preparation steps of the mixture are as follows: A1. Stir the silicon source and the structure directing agent evenly to obtain solution I; A2, deionized water is added to solution I and stirred to obtain a solution, wherein the solution is the mixture; In the step A1, the silicon source and the structure directing agent are mixed, and stirred at 25° C. for 0.5 h to 2 h to obtain solution I; In the step A2, deionized water is added to solution I, and the mixture is stirred at 25° C. for 0.5 h to 1 h to obtain a solution.
5. The method for preparing the hollow molecular sieve according to claim 3, characterized in that: In the step S2, the mixture is hydrothermally crystallized at 80°C to 200°C for 8h to 96h; and / or, the precursor I is calcined at 500° C. to 700° C. for 4 h to 8 h; And / or, the precursor I is calcined in a muffle furnace at 500° C. to 700° C. for 4 h to 8 h.
6. The method for preparing the hollow molecular sieve according to claim 3, characterized in that: The step S4 includes the following steps: B 1. Mixing the calcined precursor I with a structure directing agent solution to perform an etching reaction; The etching reaction is stirred at 50° C. to 170° C. for 1 h to 48 h; B2, separating the molecular sieve from the solution after the etching reaction by centrifugation or filtration; B3, washing the separated molecular sieve with deionized water to remove the residual structure directing agent solution and reaction by-products; B4. Centrifuge the molecular sieve after washing in B3 to separate the solid, and then dry it in an oven at 60° C. to 90° C. to obtain a hollow molecular sieve.
7. The method for preparing the hollow molecular sieve according to claim 6, characterized in that: The structure directing agent solution is a solution containing a structure directing agent, the molar concentration of the solution containing the structure directing agent is 0.1M-2M, and the feed ratio of the precursor I to the structure directing agent solution is 1g / 10ml.
8. The method for preparing a hollow molecular sieve according to claim 6, characterized in that: In the step B4, after the solid is dried in an oven, the hollow molecular sieve is calcined at a temperature of 500° C. to 700° C. for a time of 1 h to 8 h.
9. A method for preparing a molecular sieve-based flame retardant material, characterized in that: For preparing the molecular sieve-based flame retardant material according to any one of claims 1 to 2, the steps are: C 1. Introducing the flame retardant into the hollow molecular sieve by impregnation or dissolution, so that the flame retardant is partially adsorbed in the micropores and / or on the surface of the hollow molecular sieve; C2. Mixing the hollow molecular sieve containing the flame retardant with the crystallization solution, and performing a hydrothermal recrystallization reaction at 120° C. to 180° C. for 12 h to 48 h, so that the crystal structure of the hollow molecular sieve is rearranged, the micropores are reconstructed to form a hollow structure, and the flame retardant is coated or embedded in the micropores and hollow structure of the hollow molecular sieve and / or the surface of the hollow molecular sieve crystals; C3. After the recrystallization reaction is completed, the sample is separated by filtration or centrifugation, and the sample is washed with deionized water to remove the unreacted crystallization solution; C4. Drying the sample separated in step C3 to obtain a molecular sieve-based flame retardant material.
10. The method for preparing a molecular sieve-based flame retardant material according to claim 9, characterized in that: The crystallization solution is added with a structure directing agent and an alkaline solution; And / or, the crystallization solution is an aqueous solution containing a silicon source; And / or, the silicon source includes one or more of silica sol, sodium silicate, and tetraethyl silicate; the structure directing agent includes one or more of tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetraethylammonium chloride, tetrapropylammonium chloride, tetraethylammonium bromide, and tetrapropylammonium bromide; the alkaline solution is a NaOH solution or a KOH solution; In step C3, the sample is washed with deionized water to remove unreacted crystallization solution, alkaline solution and structure directing agent.
Citation Information
Patent Citations
Steel plate wall module and fireproof heat insulation steel plate protection wall
CN218643606U
Cited By
Flame retardant based on molecular sieve, preparation method of flame retardant and application of flame retardant in polyurethane adhesive
CN121362375A